Rancang Bangun Aplikasi E-Marketplace Wedding Planner Berbasis Android - Rifaldi, Muhamad; Atika, Linda (Jurnal Ilmiah Informatika Global, 2023)
Digital marketing of products can be called an e-marketplace because of the online or virtual meeting between sellers and buyers. The development of e-marketplace information technology has penetrated in various fields, one of which is wedding planners. To increase the digitalization of marketing or e-marketplaces for transactions in the marketing of wedding planner packages, it requires a system that can help entrepreneurs or people who have expertise in the field of wedding planners such as master of ceremonies, wedding organizers, building or aisle rentals, music, catering, and photographers who can carry out the package marketing process. Not only for entrepreneurs or people who have expertise, for the bride and groom also need a place to search and order from various types of wedding planner packages. The container in question is a system that can be used on a mobile basis, especially based on Android because it can make it easier for prospective brides, entrepreneurs, and people who have the expertise to carry out a process of buying and selling products or wedding planner packages. The system was built and designed using the Java programming language with MySQL as the database and firebase as the push notification. The system development methodology used is an iterative model. It is hoped that this research can produce an Android-based wedding planner e-marketplace application, so that the application can facilitate transactions for prospective brides, entrepreneurs, and people who have expertise.